Optimization of Glucose Powered Biofuel Cell Anode Developed by Polyaniline-Silver as Electron Transfer Enhancer and Ferritin as Biocompatible Redox Mediator. Issue 1 (December 2017) - Haque, Sufia; Inamuddin; Nasar, Abu; Rajender, B.; Khan, Anish; Asiri, Abdullah; Ashraf, Ghulam
Abstract Polyaniline-silver (PANI-Ag)/ferritin (Frt)/glucose oxidase (GOx) biocompatible anode was utilized for creating power from glucose. The synthesized nanocomposite was investigated by EIS (Electrochemical impedance spectroscopy), XRD (X-ray diffraction), FTIR (Fourier transform infrared spectroscopy), SEM (Scanning electron microscopy), CV (Cyclic voltammetry), and LSV (Linear sweep voltammetry) to know the morphology, crystallinity and electrochemical behaviour of the nanocomposite. The electroactive support (PANI-Ag) was utilized for the immobilization of the enzyme (GOx) and a biocompatible mediator (Frt) to enhance the electrical signals. The electrochemical estimations of the manufactured bioanode were done by utilizing cyclic voltammetry (CV) and linear sweep voltammetry (LSV). The current density obtained by the PANI-Ag/Frt/GOx bioanode was observed to be 25.40 ± 2 mA cm−2 at 40 mM of glucose concentration at a scan rate of 100 mVs−1 .